Anifrolumab has a direct immunoregulatory effect on inflamed keratinocytes: implications for the treatment of lupus erythematosus skin lesions - Kalyniuk, Ksenia; Fetter, Tanja; Grützbach, Marie; Guel, Tugce; Novak, Natalija; Wenzel, Joerg (Frontiers in Immunology, 2025)
Cutaneous lupus erythematosus (CLE) is an autoimmune skin disease characterized by a type I interferon (IFN)-driven interface dermatitis in which cytotoxic lymphocytes invade the basal layer of the epidermis and induce the keratinocytic cell death. Anifrolumab is a monoclonal antibody targeting the type I interferon receptor (IFNAR1) approved for the therapy of systemic lupus erythematosus (SLE). Recent clinical observations indicated that anifrolumab might be particularly effective in the treatment of lupus erythematosus (LE) skin manifestations. We hypothesize that anifrolumab does not only inhibit interferons circulating in the blood but also has a direct impact on keratinocytes. Our results show that IFNAR1 is expressed in lesional keratinocytes in CLE patients in immunohistochemistry. Gene expression analyses confirmed a strong activation of the interferon signaling pathway in CLE lesions. In vitro experiments with HaCaT cells, N/TERT cells and normal epidermal human keratinocyte 3D-epidermis models demonstrated that anifrolumab inhibits the expression of CLE-typical IFN-mediated proteins, including MxA and CXCL10 expression after stimulation with IFNα and synthetic and endogenous immunogenic nucleic acids. This study demonstrates that anifrolumab not only suppresses the type I IFN effect, but also inhibits other pathways of keratinocyte stimulation including pattern recognition receptor (PRR)-activation and chemokine signaling pathways, which are crucial player in the autoamplification of the proinflammatory vicious circle in CLE. These results suggest that the direct effect of anifrolumab on keratinocytes may be an important factor in its clinical efficacy in LE skin lesions and may explain the beneficial clinical effects of anifrolumab specifically in LE skin lesions.